ANALISIS KAPASITAS DAYA DUKUNG FONDASI TIANG PANCANG PADA PEMBANGUNAN GEDUNG KHATOLIK CENTER - Patrick Emillio Sahetapy; Godfried Lewakabessy; Sjafrudin Latar (Journal Agregate, 2022)
Pile bearing capacity is the ability of the pile to support the load acting on the pile. The bearing capacity of the pile foundation must be greater than the load that occurs so that it can safely hold the building. Likewise for the pile foundation used in the construction of the Catholic Center Building, which must be able to support the loads that work on it. For this reason, it is necessary to calculate the bearing capacity of single or group pile foundations to support the load of the Catholic Center Building. Many methods are used to calculate the bearing capacity of piles, one of which is by using the equation proposed by Meyerhof (1976) which uses data from the Standard Penetration Test (SPT) obtained. In this method the value of N from the SPT results is used to find the pile end resistance and pile friction resistance. From the results of the calculations, the total weight of the Catholic Center (P) building is 20462 KN. The single pile bearing capacity based on the first point is 320.2 KN and the second point is 550.7 KN. The total bearing capacity of the pile group contained in the Catholic Center Building Construction based on drilling point one is 17261 KN and drilling point two is 30179 KN. 24255 KN. Thus the pile foundation in the construction of the Catholic center building is able to safely support the weight of the building, namely Qa = 24255 KN > P = 20462 KN. Keywords: Pile Foundation, Bearing Capacity, Meyerhof